IgG-Enzyme Fusion Protein: Pharmacokinetics and Anti-Drug Antibody Response in Rhesus Monkeys - Boado, Ruben J. (2012)
The chronic administration of recombinant fusion proteins in preclinical animal models may generate an immune response and the formation of anti-drug antibodies (ADA). Such ADAs could alter the plasma pharmacokinetics of the fusion protein, and mask any underlying toxicity of the recombinant fusion protein. In the present study, a model IgG-enzyme fusion protein was evaluated with chronic dosing of Rhesus monkeys. The IgG domain of the fusion protein is a genetically engineered monoclonal antibody (MAb) against the human insulin receptor (HIR), which is shown to cross-react with the primate insulin receptor. The enzyme domain of the fusion protein is human iduronidase (IDUA), the lysosomal enzyme mutated in Mucopolysaccharidosis Type I (MPSI). MPSI affects the brain, but enzyme replacement therapy is not effective for the brain, because IDUA does not cross the blood-brain barrier (BBB). The HIRMAb domain of the fusion protein acts as a molecular Trojan horse to deliver the IDUA across the BBB. The HIRMAb-IDUA fusion protein was administered to Rhesus monkeys with weekly intravenous infusions of 3–30 mg/kg for 6 months, and the pharmacokinetics, immune response, and tissue toxicology was assessed. The pharmacokinetics of plasma clearance of the fusion protein was determined with measurements of plasma IDUA enzyme activity. ADAs formed during the course of the 6 months of treatment, as determined by a sandwich ELISA. However, the plasma clearance of the fusion protein at the start and end of the 6-month study was comparable at all drug doses. Fusion protein administration for 6 months showed no evidence of chronic tissue toxicity. These studies demonstrate that the immune response produced with chronic treatment of primates with an IgG-enzyme fusion protein has no effect on the pharmacokinetics of plasma clearance of the fusion protein.